Compact Coplanar Waveguide Metamaterial-Inspired Lines and Its Use in Highly Selective and Tunable Bandpass Filters - Borja, Alejandro L.; Kelly, James R.; Belenguer, Angel; Cascon, Joaquin; Boria, Vicente E. (IntechOpen, 2012)
None